Early-term results of early coronary artery bypass graft surgery in patients undergoing primary percutaneous coronary intervention due to acute coronary syndrome - As, Ahmet Kağan; Engin, Mesut; Turk, Tamer (The European Research Journal, 2021)
Objectives: This study aimed to investigate the early results of the patients presented with acute coronary syndrome (ACS) who underwent coronary artery bypass grafting (CABG) after percutaneous coronary intervention (PCI) to the culprit lesion.Methods: Patients who underwent CABG between January 2011 and January 2014 were enrolled and divided into two groups. Group 1 (102 patients) was consist of the patients who were hospitalized with ACS and underwent CABG after a previous PCI. Group 2 (107 patients) was consisting of the patients who underwent elective CABG operation after elective coronary angiography.Results: There was no statistically significant difference between the groups in terms of demographic features and preoperative risk factors. Preoperative use of angiotensin-converting enzyme inhibitor and levosimendan were significantly higher in group 1 compared to group 2. (95 (93.1%) vs. 89 (83.1%), p = 0.027). The operative variables were similar between two groups whereas the postoperative blood drainage amounts were significantly higher in group 1 than group 2 (546.3 ± 172 cc vs. 424.2 ± 185 cc, respectively, p < 0.001). The blood product usage was significantly higher in group 1 than in group 2 (3.3 ± 1.8 units vs.1.7 ± 0.9 units, respectively, p < 0.001).Conclusions: Early CABG operation after ACS is a safely applicable process with acceptable mortality and complication rates.